Desenvolvimento de crianças com transtorno do espectro autista por meio do inventário Portage Operacionalizado: opinião das mães - Souza, Franciele Araújo (Universidade Federal de São Carlos, 2023)
It is believed that children with Autistic Spectrum Disorder (TEA) may experience developmental delays in different ways, and areas. Thus, the study was entitled the development of children with Autism Spectrum Disorder through the portage operational inventory: mothers' opinion. Having as objectives (a) analyze the motor, linguistic, social, cognitive, and self-care development of children diagnosed with Autistic Spectrum Disorder, according to the mother’s opinion; (b) Understand the signs and diagnosis of children with Autistic Spectrum Disorder and (c) Describe the services and needs of these families. The research design was descriptive and exploratory, and it counted on the participation of three mothers of children diagnosed with ASD, between the age groups of three and five years. For data collection, the following instruments were used: (a) a semi-structured interview script; (b) a Criterion Brazil Questionnaire, and (c) Operationalized Portage Inventory (IPO). All instruments were filled out during a remote interview. Both qualitative and quantitative data were collected: the quantitative were analyzed using percentages, and the qualitative data were analyzed in the form of categories. As a result, it was identified that regarding the development of children with ASD, delay in all areas was identified through the IPO, and language was the one with the greatest impairment, followed by cognitive and motor areas. In addition, the participants indicated signs of ASD between 2 years of age. Regarding the types of signs, speech delay and not responding to a call were mentioned. All participants pointed out that children with ASD received support services, but emphasized the importance of all services being public and free. This study concluded that it is possible to verify signs of ASD in children early, and there are variations regarding different areas of development, but children had deficits in all areas. According to these results, children with ASD must have Early Childhood Intervention as soon as possible, so these deficits would be minimized.
Development of children with spectrum disorder autistics through the operationalized portage inventory: mothers' opinion
Keywords: Educação especial; Autismo; Desenvolvimento infantil; Special education; Autism; Development; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO